Temperature Fluctuations in the Lower Boundary Layer at Mizuho Station, East Antarctica - Wada, Makoto; Yamanouchi, Takashi; Mae, Shinji; Tsukamura, Koji (1981)
P(論文) Micrometeorological observations at Mizuho Station were carried out from February 1979 to January 1980 by the members of the 20th Japanese Antarctic Research Expedition (JARE-20), and will be continued until January 1982 by the other JARE members. Characteristic profiles of the temperature and the wind speed measured simultaniously from a 30m tower were analyzed. The temperature fluctuations at the level of 30m or 16m at Mizuho Station were observed. At that time, the wind speed at the 30m level was often not stronger than that at a lower level. Fluctuations of the temperature are classified into three types by the level where the phenomena appeared. When these phenomena were observed at Mizuho Station, the strong inversion layer between the surface and the height of 1000m which seemed to be caused by a large scale disturbance was observed at Syowa Station. When the katabatic wind was disturbed on a large scale these peculiar phenomena were observed at Mizuho Station. It seems that the difference of the three types depends on the relation between the large scale disturbance and the katabatic wind. departmental bulletin paper